1978
DOI: 10.1159/000176218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dietary Rapeseed Protein Concentrate on the Contents of α-Tocopherol and Zinc in Serum, Liver and Tibia of Rats

Abstract: In order to study the effects of a dietary rapeseed protein concentrate (RPC) on tocopherol and zinc levels in serum, liver and tibia, female rats were fed a tocopherol-reduced diet for a 3-week period and were then transferred to either of a RPC diet or a control diet containing casein at 20% levels of protein. No unfavourable effects on food intakes or weight gains were recorded. The serum zinc content of the RPC group was slightly reduced and the serum tocopherol values significantly lowered in comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…On the other hand, one or more components of RPC, and maybe other vegetable protein products, may by some heretofore unknown mechanism alter the metabolism of lipoproteins in such a way as to produce reduced plasma levels of lipoproteins of lower density classes. The comparatively high total lipid contents of the livers of RPC-fed rats are in agreement with a previous report (10). This finding in connection with the low plasma level of lower density lipoproteins may indicate some interference with the hepatic synthesis or secretion of lipoproteins.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, one or more components of RPC, and maybe other vegetable protein products, may by some heretofore unknown mechanism alter the metabolism of lipoproteins in such a way as to produce reduced plasma levels of lipoproteins of lower density classes. The comparatively high total lipid contents of the livers of RPC-fed rats are in agreement with a previous report (10). This finding in connection with the low plasma level of lower density lipoproteins may indicate some interference with the hepatic synthesis or secretion of lipoproteins.…”
Section: Discussionsupporting
confidence: 93%
“…Experiments carried out by Eklund and Rask (3), Eklund (9) and Eklund and Agren (10) have indicated significantly increased zinc requirements as well as decreased serum tocopherol contents in rats fed on rapeseed protein. Changes in the levels of serum lipoproteins and liver lipids were also reported from these experiments (3,10). Recently Lieden and Hambraeus (11) claimed that the toxicity of rapeseed protein for the pregnant rat was not due to phytic acid but to the presence of another distinct low molecular weight substance soluble in methanol at 65 °C.…”
Section: Introductionmentioning
confidence: 54%
“…Other studies have demonstrated effects of dietary RPC on tissue zinc (3,4) and serum tocopherol contents (4,5) in pregnant as well as non-pregnant rats. Changes in the levels of serum lipoproteins and liver lipids have also been observed in these rats (4).…”
Section: Introductionmentioning
confidence: 94%